Geological controls on the natural CO2 accumulation in the Surennuoer Oilfield of the Hailar Basin, China. (November 2021) - Yang, Jinxiu; Qi, Ning; Ireland, Mark; Lu, Shuangfang; Wang, Min; Lu, Mingyue; Xia, Ying
Abstract: Naturally occurring CO2 often coexists with hydrocarbon accumulations on continental margins around the world, the presence of which may affect hydrocarbon production as a greenhouse gas. In this paper we focus on the natural CO2 in the Surennuoer Oilfield of the Hailar Basin, and investigate CO2 origin, distribution, related tectonic controls and accumulation mechanisms using geochemical, petrophysical and seismic data. Results show that the CO2 is of inorganic origin due to the degassing of magma from the deep crust or mantle, and is mainly stored in structural traps of N1 Member. There are close spatial and temporal relationships among CO2 distribution, major fault distribution and underneath igneous bodies, indicating a genetic link. The magmatic events and major faults are proposed to be the key controlling factors of CO2 distribution, which provided CO2 supply and migration pathways for both magma and degassed CO2 . Additionally these faults also play a role in forming structural traps to store CO2 . The sandstone reservoirs of low porosity and low permeability may play a limited role due to their poor reservoir quality. Two CO2 accumulation models are outlined in the Surennuoer strike-slip fault zone and the S3 fault zone. The former is characterized by shallower magmatic igneous body and a small amount of CO2 in the shallower N2 Member in addition to N1 Member. The Surennuoer strike-slip faults may have further channelled magma upwards which initially intruded along the basin-controlling fault, while the magma under the S3 fault zone did not migrate further upward along the S3 faults. Generally this study provides a detailed understanding of CO2 distribution, accumulation models and geological controls which may guide future hydrocarbon production in the study area. Highlights: The CO2 in the Surennuor Oilfield is proposed to be of inorganic origin from magma degassing. The CO2 mainly occurs in structural traps of N1 Member. Magmatic events and faults may play the major role in controlling the CO2 accumulation. Sandstone reservoirs of poor physical properties may play a secondary role in controlling the CO2 accumulation. Two accumulation models of the natural CO2 in the study area are outlined.